Elevated levels of anti-carbamylated protein antibody in patients with rheumatoid arthritis: association with disease activity and bone destruction. (19th July 2020) - Zhang, Bei; Lei, Yimeng; Li, Xin; Gao, Ziyu; Xia, Liping; Lu, Jing; Shen, Hui
Abstract : To measure the serum levels of anticarbamylated protein (CarP) antibodies in patients with rheumatoid arthritis (RA) in China and to evaluate the association of anti-CarP antibodies with clinical parameters and disease activity. 260 Chinese patients with RA, 40 patients with osteoarthritis (OA), 88 patients with spondyloarthritis (SpA) and 77 healthy controls were included. The serum levels of anti-CarP antibodies were detected by ELISA. Blood tests to detect the anticyclic citrullinated peptide (CCP) antibody level, rheumatoid factor (RF) level, erythrocyte sedimentation rate, C reactive protein level and Disease Activity Score in 28 joints using the erythrocyte sedimentation rate (DAS28-ESR) were performed by standard methods. Bone erosion was assessed by colour Doppler ultrasonography. A total of 18.8% of patients with RA and 9.4% of anti-CCP antibody and RF-double-negative patients were positive for anti-CarP antibody. The anti-CarP antibody level was significantly higher in patients with RA than in patients with OA or SpA and in healthy controls. Univariate and multivariate analyses showed that the level of anti-CarP antibody was positively correlated with DAS28-ESR; the higher a level of serum anti-CarP antibody, the higher the DAS28-ESR score. Anti-CarP-positive patients had higher disease activity scores than anti-CarP-negative patients. Moreover, anti-CarP-positive patients had a higher risk of developing bone erosion. The anti-CarP antibody was found to play an important role in the diagnosis of RA, especially in anti-CCP antibody and RF-double-negative patients. The anti-CarP antibody is a potential marker of disease activity and bone erosion in RA.